If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 12b Solving 60 = 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. 60 + -12b = 12b + -12b Combine like terms: 12b + -12b = 0 60 + -12b = 0 Add '-60' to each side of the equation. 60 + -60 + -12b = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -12b = 0 + -60 -12b = 0 + -60 Combine like terms: 0 + -60 = -60 -12b = -60 Divide each side by '-12'. b = 5 Simplifying b = 5
| 3(x-2)=20 | | 2r^2+3=5r | | -7x-1+7(x+1)=-(6x-5) | | 17=2+y | | 2x^3-11x^2+10x+8=0 | | 0=x^2-10x+21 | | 7m+3n-7(7m-6n)= | | 7m-3=2(5m-2)+16 | | x*x+5x=12 | | 2+4y=-14 | | 6y+20=7x | | 3(-1)+y=5 | | 8x-3x+2x-9x= | | 3(1)+y=5 | | -9+3x+5x=-33 | | x+1+3x=-19 | | 1/4(8x-40) | | 3(x-4)=37-4x | | r^2+14=9r | | 24(34+r)=1248 | | 2x-5=75-8x | | -30=-7x-x+2 | | 9x+5=2x+54 | | Y-5=2(x-4) | | -2x-9+3x=-19 | | 13+5+6y+y-2= | | 2(-1)-y=1 | | -4x-3+5x=-3 | | 2(n+3)=-4 | | 2(0)-y=1 | | Y+8=-2(x-3) | | 6n+1=-13 |